Happiness [compact disc, unabridged] - Steel, Danielle (Recorded Books, Inc., 2023)
Sabrina Brooks is a successful author of gripping thrillers living a peaceful life, hiding a painful past. When she inherits an estate outside London, she plans to sell it. Why upset her stability? But a tour with handsome estate attorney Grayson Abbot makes her reconsider.